A critical comparative review of emergency and disaster management in the Arab world. Issue 1 (4th May 2021) - Al Kurdi, Osama F.
Abstract : Purpose: The Arab world is made up of 22 countries in the Middle East and North Africa. These countries are subjected to many social, economic, political and geographical vulnerabilities contributing to increased risks or ineffective emergency and disaster management. This paper examines these vulnerabilities, how they may impact the country's ability to face disasters, and how they can improve disasters' overall management. Design/methodology/approach: The author selected Qatar, Oman to represent the Arab oil-rich countries, while Jordan, Egypt and Morocco to represent non-oil rich countries. The research was conducted in a qualitative, inductive systematic literature review based on a well-established systematic literature review methodology. Selected literature was based on its recency and the countries in question. Findings: The review reveals population gaps that could threaten the social system in the event of a disaster in countries like Qatar and Oman. The majority of the countries lack community engagement and pre-planning for emergency preparedness due to social and cultural barriers. Other nations like Jordan, Egypt and Morocco are prone to long-lasting economic challenges due to lack of resources, mismanagement or corruption. The paper also highlights the need to raise the educational attainment among citizens to understand disaster risk reduction. Originality/value: This study utilized the research method developed by Williams et al. (2017) to present a comprehensive systematic and comparative review of disaster management in the Arab world. Considering that disaster and emergency management has remained disproportionately unexplored in the Arab world, this paper reviewed several vulnerabilities and how those vulnerabilities may affect disaster and emergency management efforts in the Arab countries.